rAAV-related therapy fully rescues myonuclear and myofilament function in X-linked myotubular myopathy - Ross, Jacob A. (Acta Neuropathol Commun, 2020)
X-linked myotubular myopathy (XLMTM) is a life-threatening skeletal muscle disease caused by mutations in the MTM1 gene. XLMTM fibres display a population of nuclei mispositioned in the centre. In the present study, we aimed to explore whether positioning and overall distribution of nuclei affects cellular organization and contractile function, thereby contributing to muscle weakness in this disease. We also assessed whether gene therapy alters nuclear arrangement and function. We used tissue from human patients and animal models, including XLMTM dogs that had received increasing doses of recombinant AAV8 vector restoring MTM1 expression (rAAV8-cMTM1). We then used single isolated muscle fibres to analyze nuclear organization and contractile function. In addition to the expected mislocalization of nuclei in the centre of muscle fibres, a novel form of nuclear mispositioning was observed: irregular spacing between those located at the fibre periphery, and an overall increased number of nuclei, leading to dramatically smaller and inconsistent myonuclear domains. Nuclear mislocalization was associated with decreases in global nuclear synthetic activity, contractile protein content and intrinsic myofilament force production. A contractile deficit originating at the myofilaments, rather than mechanical interference by centrally positioned nuclei, was supported by experiments in regenerated mouse muscle. Systemic administration of rAAV8-cMTM1 at doses higher than 2.5 × 10(13 )vg kg(−1) allowed a full rescue of all these cellular defects in XLMTM dogs. Altogether, these findings identify previously unrecognized pathological mechanisms in human and animal XLMTM, associated with myonuclear defects and contractile filament function. These defects can be reversed by gene therapy restoring MTM1 expression in dogs with XLMTM.